Is nutrient intake associated with physical activity levels in healthy young adults?. Issue 11 (22nd February 2016) - Yan, Yi; Drenowatz, Clemens; Hand, Gregory A; Shook, Robin P; Hurley, Thomas G; Hebert, James R; Blair, Steven N
Abstract: Objective: Both physical activity (PA) and diet are important contributors to health and well-being; however, there is limited information on the association of these behaviours and whether observed associations differ by weight. The present study aimed to evaluate whether nutrient intake is associated with PA and if this association varies by weight in young adults. Design: Cross-sectional study to analyse the association between PA and nutrient intake. Setting: Participants were stratified as normal weight (18·5 kg/m 2 <BMI <25·0 kg/m 2 ) and overweight/obese (BMI≥25·0 kg/m 2 ). PA level (PAL) was calculated (PAL=total daily energy expenditure/RMR) and used to stratify groups (PAL<1·6, 1·6≤PAL<1·9, PAL≥1·9). Subjects: Adults ( n 407; age 27·6 (sd 3·8) years, 48 % male), with BMI between 20 and 35 kg/m 2, having at least two 24 h diet recalls and at least 5 d (including two weekend days) of valid, objectively measured PA data were included in the analysis. Results: In normal-weight participants, higher PAL was associated with higher intakes of minerals (except Ca, Fe and Zn), B-vitamins and choline ( P for trend <0·05). In the overweight/obese group, higher PAL was associated with higher intakes of fibre, K, Na and Cu ( P for trend <0·05). These differences, however, were no longer significant after additionally controlling for total energy intake. Conclusions: More active young adults have higher intakes of essential micronutrients. The benefits of PA may be predominantly due to a higher overall food intake while maintaining energy balance rather than a healthier diet.